Ethanol steam reforming thermally coupled with fuel combustion in a parallel plate reactor - Lopez, Eduardo (2012)
This contribution reports experimental studies of ethanol steam reforming for the production of a hydrogen-rich reformate for fuel cells. A Pd-based catalyst, coated on corrugated metallic structures, was used. Axial concentration profiles for all components present in the system were measured in a kinetic reactor under isothermal conditions for different temperatures, flow rates, and steam-to-carbon ratios. Appropriate activity and hydrogen selectivity were achieved for this catalytic system at 650 °C, with complete ethanol conversion (no acetaldehyde), ca. 5% carbon monoxide and 1% methane as byproducts. For reactor modeling in an appropriate range of operating conditions, a simple global kinetics model is proposed; the correspondent parameters were fitted to the experimental data. Thermal coupling between ethanol steam reforming and hydrogen combustion was experimentally studied for subsequent implementation in a parallel-plate reactor, preferably in a so-called folded plate reactor. A single unit of this reactor, consisting of one combustion channel in between two halves of reforming channels was selected for the experimental proof-of-concept. The influence of different operating variables (ethanol load, feed distribution of the combustion fuel along the channel length, operation temperature, and steam-to-carbon ratio) on the reactor performance and the thermal coupling pattern will be discussed.